Evaluation of Breaking and Deshelling Machine of Roasted Cocoa Beans - Soekarno, Siswoyo; Firmansyah, Ilham; Firmanto, Hendy; Harsono, Soni Sisbudi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The manual cracking and separation of cocoa beans' husk result in low working productivity, a high percentage of broken beans, and the difficulty of separating cocoa nibs from the husk. This poses a challenge for both farmers and industrial players in cocoa bean management, leading to the development of a cocoa bean dehusking machine (desheller). This study was conducted to analyze the performance of the cocoa bean dehusking machine. The research involved motor speeds of 500, 700, and 900 rpm, combined with roasted cocoa bean grades AA, A, and B. The observed parameters included working capacity, yield, nib percentage, percentage of husk adhering to nibs, power transmission efficiency, and power requirements. The working capacity of the cocoa bean deshelling machine ranged from 17,413 to 41,481 kg/h, with yields between 73.83% and 80.83%. The nib percentage varied from 92.13% to 98.61%, while the percentage of husk adhering to nibs ranged from 1.08% to 6.92%. Power transmission efficiency was between 92.24% and 94.14%, and power requirements ranged from 601.33 to 645.33 watts. The best treatment in this study was found at a motor speed of 900 rpm with cocoa bean grade of AA.  Keywords:  Desheller,  Nibs,  Roasted cocoa beans, Shell,  Yield